A choice considered [large type] - Peterson, Tracie (Peterson, Tracie. Heart of Cheyenne, 2024)
Melody Doyle has spent years following her father as the transcontinental railroad is built. Now she's determined to stay in Cheyenne, but her father will only allow her if she marries. As the men in town vie for her hand, she gets to know the new banker, Charles Decker, who upends all her plans--and steals her heart along the way.